Parsimonious test of dynamic interaction. Issue 4 (8th February 2019) - Chisholm, Sarah; Stein, Andrew B.; Jordan, Neil R.; Hubel, Tatjana M.; Shawe‐Taylor, John; Fearn, Tom; McNutt, J. Weldon; Wilson, Alan M.; Hailes, Stephen
Abstract: In recent years, there have been significant advances in the technology used to collect data on the movement and activity patterns of humans and animals. GPS units, which form the primary source of location data, have become cheaper, more accurate, lighter and less power‐hungry, and their accuracy has been further improved with the addition of inertial measurement units. The consequence is a glut of geospatial time series data, recorded at rates that range from one position fix every several hours (to maximize system lifetime) to ten fixes per second (in high dynamic situations). Since data of this quality and volume have only recently become available, the analytical methods to extract behavioral information from raw position data are at an early stage of development. An instance of this lies in the analysis of animal movement patterns. When investigating solitary animals, the timing and location of instances of avoidance and association are important behavioral markers. In this paper, a novel analytical method to detect avoidance and association between individuals is proposed; unlike existing methods, assumptions about the shape of the territories or the nature of individual movement are not needed. Simulations demonstrate that false positives (type I error) are rare (1%–3%), which means that the test rarely suggests that there is an association if there is none. Abstract : In this paper, we introduce a novel statistical method that can be used to establish whether individuals or groups are more or less often in close proximity of each other than expected by chance. Moreover, it does so in a way that is independent of the size and shape of the individuals' ranges.